Introduction to Permaculture - Millison, Andrew (Open textbook library., 2017)
Permaculture Design is a method of land planning that can be applied at scales from the home garden to city block to village to farm. It is an ethically based whole-systems design approach that uses concepts, principles, and methods derived from ecosystems, indigenous technologies, and other time-tested practices to create sustainable human settlements and institutions. Although rooted in horticulture and agriculture, Permaculture design is interdisciplinary, touching on a wide range of subjects including regional planning, ecology, animal husbandry, appropriate technology, architecture, social justice, and international development. This open text book is derived from the content of the Massive Open Online Course “Intro to Permaculture”. The original course also included interactive mapping and design tools that accompanied this content. The course and book provide a general overview of the Permaculture design system. The book can be downloaded as a print version. However, there are many accompanying videos and content pages that are linked to throughout the text, so it is best viewed online where the links can be accessed.